Binomial Transform of the Generalized Fourth Order Pell Sequence - Yüksel Soykan (Archives of Current Research International, 2021)
In this study, we define the binomial transform of the generalized fourth order Pell sequence and as special cases, the binomial transform of the fourth order Pell and fourth order Pell-Lucas sequences will be introduced. We investigate their properties in details.